Preparation method of high-strength anti-aging plastic material
By introducing a composite of polycarbodiimide and benzotriazole UV absorbers with nano-titanium dioxide and combining it with precision processing, the problems of hydrolysis, UV aging and insufficient thermal stability of PBS materials in outdoor applications have been solved, and a high-strength anti-aging plastic material has been prepared, which is suitable for high-performance fields such as outdoor precision instruments and automotive exteriors.
Patent Information
- Application Number
- CN202511208685.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-27
- Publication Date
- 2025-12-02
AI Technical Summary
Existing PBS materials are prone to hydrolytic degradation, UV aging, and insufficient thermal stability in outdoor applications, making it difficult to meet the comprehensive requirements of high-performance fields.
By introducing polycarbodiimide anti-hydrolysis agent and benzotriazole ultraviolet absorber, and combining them with polylactic acid, nano titanium dioxide and various additives in a specific ratio under a multi-stage precision process, a polymer material system is formed, including high-speed mixing, low-temperature blending, melt reaction extrusion, rapid cooling and deep drying annealing treatment.
It achieves high strength, long-lasting hydrolysis resistance and high weather resistance of the material, significantly improving the overall durability of PBS-based materials, and is suitable for high-performance fields such as outdoor precision instruments, automotive exteriors and new energy equipment.
Smart Images

Figure CN121045757A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, and specifically discloses a method for preparing a high-strength, anti-aging plastic material. Background Technology
[0002] Polybutylene succinate (PBS), a biodegradable aliphatic polyester, has shown broad application prospects in packaging, agricultural films, and disposable products due to its excellent processing performance, mechanical properties, and biocompatibility. Simultaneously, it is attracting increasing attention in fields requiring both strength and durability, such as outdoor equipment, automotive exterior parts, and photovoltaic module encapsulation. However, inherent defects in PBS severely limit its application in high-performance fields: firstly, the ester bonds in its molecular chain are prone to hydrolysis and chain breakage under humid and hot environments, leading to a decrease in molecular weight and a sharp deterioration in mechanical properties; secondly, its resistance to ultraviolet aging is poor, easily causing yellowing, embrittlement, and surface powdering and loss of gloss under prolonged outdoor sunlight; and thirdly, its heat distortion temperature is relatively low, making it prone to creep at higher ambient temperatures and exhibiting insufficient dimensional stability.
[0003] Currently, conventional methods for improving the anti-aging properties of PBS have limitations: First, simple physical blending modification, such as blending with polylactic acid (PLA), can improve rigidity to some extent, but the two have poor compatibility and weak interfacial bonding, and the introduction of PLA often exacerbates the brittleness and hydrolysis rate of the material; second, adding conventional antioxidants and light stabilizers, these additives are prone to migration, volatilization, extraction and failure under long-term or harsh aging environments, resulting in insufficient protection durability; third, using ordinary inorganic nanoparticles (such as nano titanium dioxide) for reinforcement, if not surface treated, is prone to agglomeration, which not only makes dispersion difficult and affects mechanical properties, but may even accelerate the photo-aging degradation of the matrix resin due to photocatalytic effects.
[0004] Furthermore, existing material preparation processes are insufficient to meet high-performance requirements: traditional melt blending processes lack precise control over temperature and shear fields, making it difficult to achieve perfect compatibility and uniform dispersion of various functional additives with the resin matrix; simple cooling granulation and drying post-treatment cannot effectively eliminate internal stress and stabilize crystal morphology, resulting in poor dimensional stability and large performance fluctuations in subsequent use. These factors collectively make it difficult for existing modified PBS materials to simultaneously meet the comprehensive requirements of high strength, high hydrolysis resistance, excellent UV aging resistance, and long-term thermal stability.
[0005] Therefore, it is essential to develop a method that fundamentally and synergistically enhances [the effectiveness of] innovative component design and precise preparation processes.
[0006] High-strength anti-aging materials with excellent mechanical strength, hydrolysis resistance, and UV aging resistance have become an urgent technical requirement for expanding their application in high-value fields and meeting the requirements for long-term outdoor service. Summary of the Invention
[0007] To address the problems of hydrolytic degradation, UV aging, and insufficient thermal stability of polybutylene succinate (PBS) materials in outdoor applications, this invention discloses a method for preparing a high-strength, anti-aging plastic material. By introducing a polycarbodiimide anti-hydrolysis agent and a benzotriazole UV absorber, and combining them with polylactic acid, nano-titanium dioxide, and various additives in a specific ratio through a multi-stage precision process, a polymer material system with excellent mechanical strength, long-lasting hydrolysis resistance, and high weather resistance is constructed. This aims to synergistically improve the overall durability of PBS-based materials from the perspectives of molecular structure stability and multiple protective mechanisms. An industrially feasible preparation process has been developed, which can be widely applied in high-performance fields such as outdoor precision instruments, automotive exteriors, and new energy equipment.
[0008] The objective of this invention is achieved through the following technical solution.
[0009] A method for preparing a high-strength, anti-aging plastic material includes the following steps:
[0010] S1. Premixing the main ingredients: Add 60-80 parts by weight of polybutylene succinate and 10-20 parts by weight of polylactic acid to a high-speed mixer and mix for 5-10 minutes at 60-80℃ and 500-800 rpm.
[0011] S2, Additive stepwise mixing: Add 5-10 parts by weight of nano titanium dioxide, 3-6 parts by weight of antioxidant 1010 and 2-4 parts by weight of light stabilizer 770 to the mixture in step S1 in sequence, increase the speed of the mixer to 1000-1500 rpm and continue mixing for 10-15 minutes.
[0012] S3. Low-temperature blending of key additives: Reduce the temperature of the mixer to below 40°C, add 1-3 parts by weight of polycarbodiimide and 2-5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and mix at 800-1000 rpm for 5-8 minutes.
[0013] S4. Melt reaction extrusion: The premix obtained in S3 is fed into the main feed port of the twin-screw extruder, and 3-5 parts by weight of epoxidized soybean oil is injected through the side feed port; the temperature gradient of the extruder is set from 150℃ in zone 1 to 185℃ in zone 10, the screw speed is 300-400 rpm, and the melt blending is carried out for 5-8 minutes.
[0014] S5. Extrusion granulation and cooling: The blended melt is hot-cut by an underwater die, and after pelleting, it is rapidly cooled by chilled water at 5-10℃ to obtain pre-finished pellets with a particle size of 2-4mm.
[0015] S6. Deep drying and annealing stabilization treatment: Place the granules in a vacuum drying oven and dry them for 4-6 hours at 80-100℃ and -0.08 to -0.1MPa. Then transfer them to a hot air circulating oven and heat them from room temperature to 110-130℃ at a rate of 2℃ / min and keep them at that temperature for 2-4 hours. Then slowly cool them to room temperature at a rate of 1℃ / min to obtain the high-strength anti-aging plastic material.
[0016] Furthermore, in the above preparation method, the polylactic acid in step S1 is a mixture of L-polylactic acid (PLLA) and D-polylactic acid (PDLA) in a mass ratio of 1:1 to 1:3.
[0017] Furthermore, in the above preparation method, the nano-titanium dioxide in step S2 is rutile crystal form, and its surface is modified by silane coupling agent KH-570, with a particle size range of 20-50 nm.
[0018] Furthermore, in the above preparation method, the temperature of the ten zones of the twin-screw extruder in step S4 is specifically set as follows: Zone 1 150℃, Zone 2 160℃, Zone 3 165℃, Zone 4 170℃, Zone 5 175℃, Zone 6 180℃, Zone 7 182℃, Zone 8 180℃, Zone 9 175℃, and Zone 10 170℃.
[0019] Furthermore, in the above preparation method, the epoxy value of the epoxidized soybean oil in step S4 is ≥6.0%.
[0020] Furthermore, in the above preparation method, the annealing and stabilization treatment in step S6 is carried out under a nitrogen protective atmosphere.
[0021] This invention discloses a high-strength, anti-aging plastic material, which is prepared by any of the methods described above.
[0022] Furthermore, the aforementioned high-strength, anti-aging plastic materials meet the following performance indicators:
[0023] a) Tensile strength: ≥45MPa;
[0024] b) Elongation at break: ≥300%;
[0025] c) Heat distortion temperature (1.82 MPa): ≥120℃;
[0026] d) Tensile strength retention rate after 2000 hours of UV aging: ≥90%;
[0027] e) Color difference ΔE after 1000 hours of xenon lamp aging: ≤3.0;
[0028] f) Impact strength (notched): ≥15kJ / m 2 .
[0029] Furthermore, the aforementioned high-strength anti-aging plastic material, after aging for 1000 hours at 85°C and 85% relative humidity, retains ≥85% of its flexural strength and has a weight change rate ≤1.5%.
[0030] This invention also discloses the application of the above-mentioned high-strength anti-aging plastic material in the housing of outdoor precision instruments, automotive exterior parts, or photovoltaic module encapsulation frames.
[0031] Compared with existing technologies, the present invention has the following advantages and beneficial effects:
[0032] 1. Synergistic Anti-aging Performance: By introducing polycarbodiimide (PCDI) as a highly efficient anti-hydrolysis agent, it reacts with the carboxyl groups at the ends of the PBS molecular chains, effectively sealing the hydrolytic active sites and fundamentally inhibiting the chain-breaking reaction of ester bonds under humid and hot conditions. This allows the material to maintain more than 85% of its flexural strength after aging at 85℃ / 85%RH for 1000 hours. Simultaneously, a specific benzotriazole ultraviolet absorber (UV-P) is combined with surface-treated rutile nano-titanium dioxide. The two work synergistically in terms of UV protection. The nano-titanium dioxide physically reflects / scatters ultraviolet light, while the UV-P molecules efficiently absorb and convert ultraviolet light energy, jointly constructing a strong ultraviolet barrier. This results in a tensile strength retention rate of over 90% after 2000 hours of UV aging, with minimal color change (ΔE≤3.0), greatly extending its outdoor service life.
[0033] 2. Excellent comprehensive mechanical properties and thermal stability: By using PLA blended with L-polylactic acid (PLLA) and D-polylactic acid (PDLA), and forming a well-compatible system with PBS, the material not only enhances strength and rigidity but also avoids the brittleness associated with single-component PLA. Combined with the rigid particle reinforcement effect of nano-titanium dioxide and the compatibilizing and plasticizing effect of epoxidized soybean oil, the material maintains high tensile strength (≥45MPa) and high impact toughness while significantly increasing the heat distortion temperature to over 120℃. A unique programmed temperature annealing process effectively eliminates internal stress, stabilizes the crystal morphology, and ensures long-term dimensional stability and performance consistency of the finished product.
[0034] 3. Advanced process, suitable for industrial production: The multi-stage mixing and precise temperature control extrusion-cooling-annealing integrated process designed in this invention ensures the uniform dispersion and good compatibility of various functional additives in the resin matrix, preventing additive failure due to migration and volatilization, and guaranteeing the durability of performance protection. The entire preparation process is efficient and controllable, providing a reliable technical route for large-scale industrial production of high-performance, long-life PBS-based engineering plastics. Attached Figure Description
[0035] Figure 1Performance changes after 2000 hours of UV aging: tensile strength retention rate (%);
[0036] Figure 2 Performance changes after 2000 hours of UV aging: color difference ΔE;
[0037] Figure 3 Performance changes after 1000 hours of damp heat aging: flexural strength retention rate (%);
[0038] Figure 4 Performance changes after 1000 hours of damp heat aging: weight change rate (%);
[0039] Figure 5 Comparison of oxidation induction time (OIT). Detailed Implementation
[0040] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below. However, it should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concept of the invention. All raw materials used in the embodiments of this invention are commercially available.
[0041] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.
[0042] Table 1 below is a table of raw material parameters for this invention.
[0043] Table 1: Raw Material Table
[0044]
[0045] Example 1
[0046] A method for preparing a high-strength, anti-aging plastic material includes the following steps:
[0047] S1. Premixing of main ingredients: Add 60 parts by weight of polybutylene succinate (PBS) and 20 parts by weight of polylactic acid (PLA, PLLA and PDLA are compounded in a mass ratio of 1:1) to a high-speed mixer and mix for 10 minutes at 60°C and 800 rpm.
[0048] S2. Additive stepwise mixing: Add 5 parts by weight of KH-570 treated nano titanium dioxide (rutile type, particle size 30nm), 6 parts by weight of antioxidant 1010, and 2 parts by weight of light stabilizer 770 to the mixture in step S1 in sequence. Increase the speed of the mixer to 1500rpm and continue mixing for 10 minutes.
[0049] S3. Low-temperature blending of key additives: Cool the mixer to 35°C, add 1 part by weight of polycarbodiimide (PCDI) and 5 parts by weight of ultraviolet absorber UV-P, and mix at 1000 rpm for 5 minutes.
[0050] S4. Melt reaction extrusion: The premix obtained in S3 is fed into the main feed port of a twin-screw extruder, and 3 parts by weight of epoxidized soybean oil (epoxidation value 6.2%) is injected through the side feed port; the extruder is set to ten zones of temperature (zone 1 150℃, zone 2 160℃, zone 3 165℃, zone 4 170℃, zone 5 175℃, zone 6 180℃, zone 7 182℃, zone 8 180℃, zone 9 175℃, zone 10 170℃), and the screw speed is 400 rpm, and melt-blending is performed for 5 minutes;
[0051] S5. Extrusion granulation and cooling: The blended melt is hot-cut by an underwater die, and after pelleting, it is rapidly cooled by 8°C chilled water to obtain particles with a diameter of 3mm.
[0052] S6. Deep drying and annealing stabilization treatment: Place the particles in a vacuum drying oven and dry them at 100℃ and -0.09MPa for 4 hours; then, under nitrogen protection, raise the temperature to 110℃ at a rate of 2℃ / min and hold for 4 hours, and then slowly cool to room temperature at a rate of 1℃ / min to obtain the finished material.
[0053] Example 2
[0054] A method for preparing a high-strength, anti-aging plastic material includes the following steps:
[0055] S1. Premixing of main ingredients: Add 70 parts by weight of PBS and 15 parts by weight of PLA (PLLA and PDLA are mixed in a mass ratio of 1:2) into a high-speed mixer and mix for 15 minutes at 70°C and 600 rpm.
[0056] S2. Additive stepwise mixing: Add 8 parts by weight of KH-570 treated nano titanium dioxide (rutile type, particle size 40nm), 4 parts by weight of antioxidant 1010 and 3 parts by weight of light stabilizer 770 to the mixture in step S1 in sequence, increase the speed of the mixer to 1200rpm and continue mixing for 12 minutes.
[0057] S3. Low-temperature blending of key additives: Cool the mixer to 30°C, add 2 parts by weight of PCDI and 3 parts by weight of UV-P, and mix at 900 rpm for 7 minutes.
[0058] S4. Melt reaction extrusion: The premix obtained in S3 is fed into a twin-screw extruder, and 4 parts by weight of epoxidized soybean oil (epoxidation value 6.5%) is injected through the side feed port; the extruder is set to the ten-zone temperature (temperature gradient from the same zone to the tenth zone), the screw speed is 350 rpm, and the melt blending is carried out for 7 minutes.
[0059] S5. Extrusion granulation and cooling: The blended melt is hot-cut by an underwater die, and after pelleting, it is rapidly cooled by 5℃ chilled water to obtain particles with a particle size of 2mm.
[0060] S6. Deep drying and annealing stabilization treatment: Place the particles in a vacuum drying oven and dry them at 90℃ and -0.1MPa for 5 hours; then, under nitrogen protection, raise the temperature to 120℃ at a rate of 2℃ / min and hold for 3 hours, and then slowly cool to room temperature at a rate of 1℃ / min to obtain the finished material.
[0061] Example 3
[0062] A method for preparing a high-strength, anti-aging plastic material includes the following steps:
[0063] S1. Premixing of main ingredients: Add 80 parts by weight of PBS and 10 parts by weight of PLA (PLLA and PDLA are mixed in a mass ratio of 1:3) into a high-speed mixer and mix for 20 minutes at 80°C and 500 rpm.
[0064] S2. Additive stepwise mixing: Add 10 parts by weight of KH-570 treated nano titanium dioxide (rutile type, particle size 20nm), 3 parts by weight of antioxidant 1010, and 4 parts by weight of light stabilizer 770 to the mixture in step S1 in sequence. Increase the speed of the mixer to 1000 rpm and continue mixing for 15 minutes.
[0065] S3. Low-temperature blending of key additives: Cool the mixer to 25°C, add 3 parts by weight of PCDI and 2 parts by weight of UV-P, and mix at 800 rpm for 8 minutes.
[0066] S4. Melt reaction extrusion: The premix obtained in S3 is fed into a twin-screw extruder, and 5 parts by weight of epoxidized soybean oil (epoxidation value 6.8%) is injected through the side feed port; the extruder is set to the ten-zone temperature (temperature gradient from the same zone to the tenth zone), the screw speed is 300 rpm, and the melt blending is carried out for 8 minutes.
[0067] S5. Extrusion granulation and cooling: The blended melt is hot-cut by an underwater die, and after pelleting, it is rapidly cooled by 5℃ chilled water to obtain particles with a particle size of 4mm.
[0068] S6. Deep drying and annealing stabilization treatment: Place the particles in a vacuum drying oven and dry them at 80℃ and -0.08MPa for 6 hours; then, under nitrogen protection, raise the temperature to 130℃ at a rate of 2℃ / min and hold for 2 hours, and then slowly cool to room temperature at a rate of 1℃ / min to obtain the finished material.
[0069] Comparative Example 1
[0070] PBS main ingredient replacement comparison
[0071] A method for preparing a plastic material, the formulation and steps of which are exactly the same as those in Example 2, the only difference being that in step S1, polybutylene succinate (PBS) is replaced with an equal amount of polypropylene (PP, grade K8303).
[0072] Comparative Example 2
[0073] PLA Main Ingredient Replacement Comparison
[0074] A method for preparing a plastic material, the formula and steps of which are exactly the same as those in Example 2, the only difference being that in step S1, polylactic acid (PLA) is replaced with an equal amount of polyethylene terephthalate (PET).
[0075] Comparative Example 3
[0076] Complete replacement comparison of PBS / PLA systems
[0077] A method for preparing a plastic material, the formulation and steps of which are exactly the same as those in Example 2, the only difference being: in step S1, polybutylene succinate (PBS) and polylactic acid (PLA) are completely replaced with equal amounts of high-density polyethylene (HDPE), and polycarbodiimide (PCDI) in step S3 is omitted (because...).
[0078] HDPE does not require hydrolysis resistance.
[0079] Comparative Example 4
[0080] Inorganic filler reinforcement comparison
[0081] A method for preparing a plastic material, the formula and steps of which are exactly the same as those in Example 2, the only difference being that in step S1, "polylactic acid (PLA)" is replaced with an equal amount of "calcium carbonate (CaCO3)".
[0082] Comparative Example 5
[0083] Comparison of anti-hydrolysis agent replacements
[0084] A method for preparing a plastic material, the formulation and steps of which are exactly the same as those in Example 2, the only difference being that in step S3, the "polycarbodiimide (PCDI) anti-hydrolysis agent is replaced with an equal amount of carbodiimide (STABAXOL P100)".
[0085] Comparative Example 6
[0086] Comparison of UV absorber replacements
[0087] A method for preparing a plastic material, the formula and steps of which are exactly the same as those in Example 2, the only difference being that in step S3, the ultraviolet absorber UV-P is replaced with an equal amount of ultraviolet absorber UV-234.
[0088] Comparative Example 7
[0089] Nanoparticle replacement comparison
[0090] A method for preparing a plastic material, the formula and steps of which are exactly the same as those in Example 2, the only difference being that in step S2, the nano titanium dioxide (rutile type) treated with KH-570 is replaced with an equal amount of nano zinc oxide (ZnO) treated in the same way.
[0091] Test Example 1
[0092] Basic mechanical and thermal performance testing
[0093] Objective: To verify whether the material prepared by this invention meets or exceeds the basic performance indicators claimed in the specification.
[0094] method:
[0095] Sample preparation: After drying the material particles obtained in Examples 1-3 and Comparative Examples 1-7 at 100°C for 4 hours, they were injection molded into standard test specimens (tensile specimen: ASTM D638 Type I; impact specimen: ASTM D256 withnotch; bending specimen: ASTM D790) using an injection molding machine.
[0096] Testing standards:
[0097] Tensile strength and elongation at break: Tested according to ASTM D638 standard using a universal testing machine (model: Instron5967) at a tensile rate of 50 mm / min.
[0098] Impact strength: Tested according to ASTM D256 using a cantilever beam impact testing machine (model: Instron Ceast9050).
[0099] Heat distortion temperature (HDT): Tested according to ASTM D648 standard, with a load of 1.82 MPa, using a heat distortion testing machine (model: Ceast HDT 3VICAT).
[0100] Results: See Table 2.
[0101] Table 2: Test Results of Basic Mechanical and Thermal Properties
[0102]
[0103]
[0104] Note: Comparative Example 3 (HDPE) has good toughness, but its strength and heat resistance are far inferior to those of this invention.
[0105] Conclusion: The mechanical properties of the three embodiments of the present invention are excellent, fully meeting and slightly exceeding the preset targets (tensile strength ≥ 45 MPa, elongation at break ≥ 300%, impact strength ≥ 15 kJ / m). 2 (HDT≥120℃). Comparative Examples 1 (PP), 2 (PET), and 4 (CaCO3) exhibited poor compatibility with the PBS / PLA system, resulting in a significant decrease in toughness (elongation at break and impact strength). Comparative Example 5 (replacing PCDI) showed a decrease in elongation at break, indicating potentially insufficient hydrolytic stability. Comparative Examples 6 (replacing the UV absorber) and 7 (replacing nanoparticles) showed properties similar to the examples, but subsequent aging tests will reveal their differences. This demonstrates that the component design and process of the present invention can effectively synergize, endowing the material with comprehensive properties of high strength, high toughness, and heat resistance.
[0106] Test Example 2
[0107] UV aging resistance test
[0108] Objective: To evaluate the color stability and mechanical property retention of the material under long-term ultraviolet irradiation.
[0109] method:
[0110] UV aging: Place each set of test strips into a UV aging test chamber (model: Q-LAB QUV / spray). The test conditions are in accordance with ASTM G154 Cycle 1: UVB-313 lamp, 60℃ UV irradiation for 8 hours, 50℃ condensation for 4 hours, and repeat.
[0111] Performance evaluation:
[0112] Color difference (ΔE): The color difference ΔE value of the sample surface was measured using a colorimeter (model: X-Rite Ci64) at 0 hours, 500 hours, 1000 hours, 1500 hours and 2000 hours of aging.
[0113] Mechanical property retention rate: After aging for 2000 hours, the tensile strength of the test specimen is measured, and its retention rate relative to the unaged specimen is calculated.
[0114] Results: See Table 3 and Figure 1-2 .
[0115] Table 3: Performance changes after 2000 hours of UV aging
[0116] Group Tensile strength retention rate (%) Color difference ΔE Example 2 92.5 2.8 Comparative Example 5 78.3 4.5 Comparative Example 6 85.1 6.2* Comparative Example 7 70.4 3.9
[0117] *Note: Comparative Example 6 (UV-234) is significantly inferior to UV-P used in this invention in terms of its ability to resist yellowing.
[0118] Conclusion: After undergoing rigorous 2000 hours of UV aging, the material of this invention (Example 2) maintained a tensile strength retention rate of over 90% and a color difference ΔE of less than 3.0, demonstrating excellent UV aging resistance. Comparative Examples 5 (anti-hydrolysis agent replacement) and 7 (nanoparticle replacement) showed significantly reduced strength retention rates, indicating that PCDI and rutile nano-TiO2 in the original formulation made significant contributions to UV stability. Comparative Example 6 (UV absorber replacement) exhibited severe yellowing (high ΔE value), proving that the specific benzotriazole UV absorber (UV-P) selected in this invention has unique advantages in inhibiting material discoloration.
[0119] Test Example 3
[0120] Resistance to damp heat aging (hydrolysis resistance) performance test
[0121] Objective: To evaluate the long-term durability and hydrolysis resistance of the material under high temperature and high humidity conditions.
[0122] method:
[0123] Humid heat aging: The test strips were placed in a constant temperature and humidity test chamber (model: ESPEC PL-3J) and the conditions were set to 85℃ and 85% relative humidity (RH).
[0124] Performance evaluation: Samples were taken out at 0 hours, 500 hours and 1000 hours respectively, wiped clean and equilibrated for 24 hours in a standard laboratory environment.
[0125] Weight change rate: Accurately weigh the weight change of the sample before and after aging.
[0126] Bending strength retention rate: Test bending strength according to ASTM D790 and calculate the retention rate.
[0127] Results: See Table 4 and Figure 3 and Figure 4 .
[0128] Table 4: Performance changes after 1000 hours of damp heat aging
[0129] Group Bending strength retention rate (%) Weight change rate (%) Example 2 87.2 +1.2 Comparative Example 5 62.5 +3.8 Comparative Example 7 80.1 +1.5
[0130] Conclusion: After 1000 hours of harsh aging at double 85%, the material of this invention maintained over 85% of its flexural strength with an extremely low weight gain (1.2%), indicating that polycarbodiimide (PCDI) effectively capped the terminal carboxyl groups and ester bonds of the PBS molecular chain, significantly inhibiting the water molecule-induced cleavage reaction. Comparative Example 5 (PCDI replacement) showed a sharp decline in performance and a large weight change rate, proving that PCDI is an indispensable key anti-hydrolysis component. Comparative Example 7 (nano ZnO) showed acceptable performance but not as good as the examples, possibly related to the stability of ZnO under different pH conditions, further demonstrating the applicability of rutile TiO2.
[0131] Test Example 4
[0132] Long-term thermal oxidative stability test (OIT)
[0133] Objective: To evaluate the material's resistance to thermal oxidation at high temperatures through oxidation induction period testing.
[0134] method:
[0135] Test standard: in accordance with ASTM D3895.
[0136] Instrument: Differential scanning calorimeter (DSC, model: TA Instruments Q20).
[0137] Procedure: Take about 5 mg of sample and heat it to 200 °C at 20 °C / min under a nitrogen atmosphere. After equilibrium is reached, quickly switch to an oxygen atmosphere (50 mL / min). Record the start time of the exothermic oxidation reaction of the sample, which is the oxidation induction time (OIT).
[0138] Results: See Table 5 and Figure 5 .
[0139] Table 5: Comparison of Oxidation Induction Time (OIT) @200℃
[0140] Group OIT (minutes) Example 2 42.5 Pure PBS 8.1 Comparative Example 1 35.7 Comparative Example 4 25.6
[0141] Conclusion: The OIT value of the material of this invention is much higher than that of pure PBS, indicating a significant improvement in its thermal oxidation stability. This is attributed to the synergistic effect of antioxidant 1010 and light stabilizer 770, as well as the good compatibility and dispersibility of the entire system. The lower OIT values of Comparative Examples 1 (PP-based) and 4 (CaCO3-filled) indicate that their stabilization systems are insufficient to cope with long-term thermal oxidation aging, which also indirectly proves the superior compatibility between the PBS / PLA matrix and the additive system of this invention.
[0142] Overall conclusion:
[0143] The above series of tests demonstrate that the high-strength anti-aging plastic material preparation method provided by this invention, through the core role of polycarbodiimide (PCDI) and a specific benzotriazole ultraviolet absorber (UV-P), combined with surface-treated nano-titanium dioxide and optimized PLA, and under precise temperature control and annealing processes, successfully prepares a material with excellent comprehensive performance. This material not only possesses excellent initial mechanical strength and heat resistance, but more importantly, it exhibits long-lasting resistance to ultraviolet aging, excellent hydrolysis resistance, and high thermal stability, overcoming the inherent defects of traditional PBS materials and fully meeting the application requirements of high-end fields such as outdoor precision instruments and automotive exterior parts. The test results of each comparative example highlight the necessity and synergy of each component in the formulation and process of this invention.
[0144] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, any changes and modifications made to the embodiments described herein based on the innovative concept of the present invention, or equivalent structural or procedural transformations made using the content of the present invention specification, directly or indirectly applying the above technical solutions to other related technical fields, are all included within the scope of protection of the present invention patent.
Claims
1. A method for preparing a high-strength, anti-aging plastic material, characterized in that, Includes the following steps: S1. Premixing the main ingredients: Add 60-80 parts by weight of polybutylene succinate and 10-20 parts by weight of polylactic acid to a high-speed mixer and mix for 5-10 minutes at 60-80℃ and 500-800 rpm. S2, Additive stepwise mixing: Add 5-10 parts by weight of nano titanium dioxide, 3-6 parts by weight of antioxidant 1010 and 2-4 parts by weight of light stabilizer 770 to the mixture in step S1 in sequence, increase the speed of the mixer to 1000-1500 rpm and continue mixing for 10-15 minutes. S3. Low-temperature blending of key additives: Reduce the temperature of the mixer to below 40°C, add 1-3 parts by weight of polycarbodiimide and 2-5 parts by weight of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and mix at 800-1000 rpm for 5-8 minutes. S4. Melt reaction extrusion: The premix obtained in S3 is fed into the main feed port of the twin-screw extruder, and 3-5 parts by weight of epoxidized soybean oil is injected through the side feed port; the temperature gradient of the extruder is set from 150℃ in zone 1 to 185℃ in zone 10, the screw speed is 300-400 rpm, and the melt blending is carried out for 5-8 minutes. S5. Extrusion granulation and cooling: The blended melt is hot-cut by an underwater die, and after pelleting, it is rapidly cooled by chilled water at 5-10℃ to obtain pre-finished pellets with a particle size of 2-4mm. S6. Deep drying and annealing stabilization treatment: Place the granules in a vacuum drying oven and dry them for 4-6 hours at 80-100℃ and -0.08 to -0.1MPa. Then transfer them to a hot air circulating oven and heat them from room temperature to 110-130℃ at a rate of 2℃ / min and keep them at that temperature for 2-4 hours. Then slowly cool them to room temperature at a rate of 1℃ / min to obtain the high-strength anti-aging plastic material.
2. The preparation method according to claim 1, characterized in that, The polylactic acid mentioned in step S1 is a mixture of L-polylactic acid (PLLA) and D-polylactic acid (PDLA) in a mass ratio of 1:1 to 1:
3.
3. The preparation method according to claim 1, characterized in that, The nano-titanium dioxide mentioned in step S2 is rutile crystal form, and its surface is modified by silane coupling agent KH-570, with a particle size range of 20-50 nm.
4. The preparation method according to claim 1, characterized in that, The specific temperature settings for the ten zones of the twin-screw extruder in step S4 are as follows: Zone 1 150℃, Zone 2 160℃, Zone 3 165℃, Zone 4 170℃, Zone 5 175℃, Zone 6 180℃, Zone 7 182℃, Zone 8 180℃, Zone 9 175℃, and Zone 10 170℃.
5. The preparation method according to claim 1, characterized in that, The epoxy value of the epoxidized soybean oil described in step S4 is ≥6.0%.
6. The preparation method according to claim 1, characterized in that, The annealing and stabilization treatment described in step S6 is carried out under a nitrogen protective atmosphere.
7. A high-strength, anti-aging plastic material, characterized in that, Prepared by the method described in any one of claims 1-6.
8. The high-strength anti-aging plastic material according to claim 7, characterized in that, Its performance meets the following specifications: a) Tensile strength: ≥45MPa; b) Elongation at break: ≥300%; c) Heat distortion temperature (1.82 MPa): ≥120℃; d) Tensile strength retention rate after 2000 hours of UV aging: ≥90%; e) Color difference ΔE after 1000 hours of xenon lamp aging: ≤3.0; f) Impact strength (notched): ≥15kJ / m 2 .
9. The high-strength anti-aging plastic material according to claim 8, characterized in that, After aging at 85°C and 85% relative humidity for 1000 hours, the material retains ≥85% of its bending strength and has a weight change rate ≤1.5%.
10. The application of the high-strength anti-aging plastic material as described in claim 7 in outdoor precision instrument housings, automotive exterior parts, or photovoltaic module encapsulation frames.
Citation Information
Patent Citations
Rigidity-toughness balanced polylactic acid-based biodegradable material and preparation method thereof
CN116144149A